1975
DOI: 10.1103/physrevb.12.3453
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced tunnel currents in Al-Al2O3-Au structures

Abstract: A study of photo-induced tunnel currents in Al-A1~03-Au diode structures is presented. It includes measurements of both spectral dependence and voltage dependence. The experimental results obtained can be accounted for by an analysis based on the trapezoidal model for the oxide barrier shape. The data suggest that hot-electron attenuation in the A1203 layer is insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Understanding the physics of EBIC imaging in resistive switching devices has broader implications for the metrology of resistive switching. The direct observation of hot electron currents, for example, opens the door to other hot electron techniques such as ballistic electron emission microscopy (BEEM) and internal photoemission (IPE) [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the physics of EBIC imaging in resistive switching devices has broader implications for the metrology of resistive switching. The direct observation of hot electron currents, for example, opens the door to other hot electron techniques such as ballistic electron emission microscopy (BEEM) and internal photoemission (IPE) [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…IPE, being the optical analog to EBIC, sacrifices spatial resolution for precise spectroscopic information. While IPE has long been used to study MIM diodes and other electronic devices 59,61 , its use has not been demonstrated on filaments, probably due to the small active area. An IPE system, most likely combined with high brightness sources, focusing optics and phase sensitive detection, could make it possible to deconstruct the underlying electronic structure of the filament-electrode interface as a function of state.…”
Section: Discussionmentioning
confidence: 99%
“…The molecule-lead coupling is distributed among the replicas where the coupling matrix element is proportional to the l th Fourier component of the (transformed) periodic field. Formally, one obtains where is a generalized Fermi function, 23 corresponding to the nonequilibrium state of the driven lead. The displaced functions, f l ( K ) ( E ) = f ( K ) ( E – ℏωl ) are expressed in terms of the nondriven lead Fermi function, , where μ K is the lead chemical potential and T is the temperature.…”
mentioning
confidence: 99%
“…These expressions are described extensively in refs. [13][14][15][16][17][18].As stated before the lanthanide ions form double layers perpendicular to the c-axis. The distance between these layers (-10 A) is considerably larger than the distance between two lanthanide ions in the layers (- 3.7 A).…”
Section: Discussionmentioning
confidence: 98%